Adoption of Certified Seeds by Farmers: A Perspective from the Theory of Trying - Shine Pintor Siolemba Patiro; Prisila Damayanti; Endi Rekarti (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2026)
This study aims to analyze the adoption of certified seeds by farmers using the perspective of the Theory of Trying. The study is motivated by the importance of using certified seeds to improve productivity and sustainability in the agricultural sector; however, adoption rates vary among farmers. The research involves 473 farmers who are members of farmer groups and are located in the provinces of Banten, West Java, Central Java, and East Java. A purposive sampling technique was used to select participants. Data were collected through structured questionnaires and analyzed using Structural Equation Modeling (SEM) to test the relationships between variables in the research model. The results show that all hypotheses were significantly supported, indicating that constructs in the Theory of Trying, such as attitude toward the process of trying, subjective norms, attitude toward the success of trying, attitude toward the failure of trying, and attitude toward trying behavior, play an important role in encouraging the intention and behavior of farmers to adopt certified seeds. These findings provide theoretical implications for the development of adoption behavior models for agricultural technology and practical implications for governments and stakeholders in designing more effective policies and programs to increase the use of certified seeds among farmers.